EXPLORING INTEREST GEN Z INVESTMENT IN THE STOCK MARKET: STUDIES EMPIRICAL IN SURABAYA CITY - Aryasatya, Laudza; Setiobudi, Auditia; Teofilus, Teofilus; Darsana, Ni Putu Andini Kusuma Putri (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This study is for learning attitude, subjective norms, and perception control behavior, which can influence interest in investing Surabaya students in the capital market. The research uses quantitative methodology. Besides that, the method of taking a purposive sample was used for the retrieval process sample. Data was collected through a distribution questionnaire to 110 respondents from University Ciputra and the University Airlangga who have invested in the capital market. An online questionnaire was used to collect data. Online questionnaires refer to Google Forms as a medium for filling out questionnaires. The collected data was processed using the Partial Least Square method with the analysis software SmartPLS 3, which aims to test the connectedness between variables. Testing this shows that attitude, subjective norms, and perceived behavioral control have significant connections to interest investment students in Surabaya City in investing in the stock market. Implications study this is to encourage the Indonesian Stock Exchange as a regulator, companies as intermediary trading shares, and companies engaged in the finance field to collaborate to give education and insight into investment shares among students.